Cell adaptation of the extremophilic red microalga Galdieria sulphuraria to the availability of carbon sources - Perez Saura, Pablo; Chabi, Malika; Corato, Amélie; Cardol, Pierre; Remacle, Claire (Frontiers in Plant Science, 2022)
Global energy demand and fossil fuels impact on climate can be partially managed by an increase in the use of biofuels for transports and industries. Biodiesel production is generally preceded by a transesterification process of the green biomass triacylglycerols that generates large amounts of glycerol as a by-product. In this study, the extremophilic red microalga Galdieria sulphuraria 074W was cultivated in heterotrophy. The microalgal growth parameters and biomass composition were compared when grown on an equivalent molar concentration of carbon of either glucose or glycerol as unique carbon source. The maximal biomass reached in these two conditions was not significantly different ( 2.5 g.L-1). Fatty acid profile, protein and storage carbohydrate contents were also statistically similar, irrespectively of the metabolised carbon source. We also observed that the pigment content of G. sulphuraria cells decreased during heterotrophic growth compared to photoautotrophic cultivated cells, and that this diminution was more important in the presence of glucose than glycerol: cells were yellowish in the presence of glucose and green in the presence of glycerol. The pigmentation was restored when glucose was totally consumed in the medium, suggesting that the presence of glucose repressed pigment synthesis. Based on this observation, a transcriptome analysis was performed in order to better understand the mechanisms involved in the loss of color mediated by darkness and by glucose in G. sulphuraria. Three conditions were analyzed: heterotrophy with glycerol or glucose and phototrophy. This allowed us to understand the transcriptional response of cells to light and dark environments both at the nuclear and chloroplast levels, and to show that transcription of gene families, acquired by horizontal gene transfer, such as sugar, amino acid or acetate transporters, were involved in the response to the availability of different (in)organic sources.